Non-topological, topological and rogue wave Soliton solutions for Sharma Tasso Olver equation - Zafar, Zain Ul Abadin; Akinyemi, Lanre; Rezazadeh, Hadi; İnç, Mustafa (Shanghai Jiaotong University, 2022)
This paper proposes three types of envelope solitons for the Sharma-Tasso-Olver equation with power-law nonlinearity. The ansatz approach is used to investigate the presence of these solitons identified during the solution derivation. As a result, we acquired the bright, singular, and dark solitons, which have a wide range of applications in applied science and engineering. Furthermore, the physical structures of the obtained solitons are investigated using two-dimensional, three-dimensional, and three-dimensional revolution plots with varying parameter values. © 2022
Keywords: Non-topological solitons; Rogue wave soliton; Sharma-Tasso-Olver (STO) equation; Solitary wave ansatz; Topological solitons